2016
DOI: 10.1007/s10803-016-2751-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence of Atypical Spatial Attention in Those with a High Level of Self-reported Autistic Traits

Abstract: Selective attention is atypical in individuals with autism spectrum conditions. Evidence suggests this is also the case for those with high levels of autistic traits. Here we investigated the neural basis of spatial attention in those with high and low levels of self-reported autistic traits via analysis of ERP deflections associated with covert attention, target selection and distractor suppression (the N2pc, N T and P D ). Larger N2pc and smaller P D amplitude was observed in those with high levels of autist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…In contrast to the findings, we report here, previous research in ASD and the BAP has also pointed to increased distractor interference or increased sensitivity to salience seen in this population in certain conditions [Leader et al, ]. For instance, in a recent study using EEG to record brain potentials, Dunn, Freeth, and Milne [] identified reduced Pd (which is thought to represent distractor suppression) in individuals with high autistic traits compared to those with low autistic traits. This also fits with other finding suggesting a failure of participants with ASD to suppress a salient distractor [e.g., Russell et al, ] or examples where behavior is dominated by the salient stimulus in ASD [e.g., Leader et al, ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the findings, we report here, previous research in ASD and the BAP has also pointed to increased distractor interference or increased sensitivity to salience seen in this population in certain conditions [Leader et al, ]. For instance, in a recent study using EEG to record brain potentials, Dunn, Freeth, and Milne [] identified reduced Pd (which is thought to represent distractor suppression) in individuals with high autistic traits compared to those with low autistic traits. This also fits with other finding suggesting a failure of participants with ASD to suppress a salient distractor [e.g., Russell et al, ] or examples where behavior is dominated by the salient stimulus in ASD [e.g., Leader et al, ].…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, previous research has shown that when encouraged to use such control strategy—for instance when given full instruction in terms of which part of a face to attend, atypicalities in face processing in ASD can be overcome [Kikuchi et al, ; Kikuchi et al, ]. Similarly, in Dunn et al [] the reported smaller Pd amplitude associated with reduced distractor suppression was evidenced later in the process—after stimuli presentation, which may point to reactive suppression rather than a preparatory one. It is therefore plausible to speculate that increased distractor suppression (as we report here) in the BAP is associated with enhanced preparatory top‐down control.…”
Section: Discussionmentioning
confidence: 95%
“…We suggest that the dual mechanisms theory of proactive and reactive cognitive control 39 may provide a framework to understand the contrasting effects of autism and psychosis traits we observed in neurotypical individuals, and by extension, the inconsistencies in the literature on attention atypicalities in ASD and SSD 5 , 6 , 13 , 40 , 41 . In proactive control, individuals bias attention by maintaining goal-relevant information and preventing interference in an anticipatory manner even before the onset of the stimulus.…”
Section: Discussionmentioning
confidence: 81%
“…In SSD, the effect of salient distractors on target selection has been associated with both interference 2 5 , and lack of interference, and even benefit (when attention is guided by bottom-up information) 5 , 6 . Similarly, in ASD, there is evidence for both reduced typical levels of interference 7 9 , as well as increased processing cost 10 13 in the presence of salient distractors. Thus, the contexts under which ASD and SSD and their expressions in neurotypicals yield beneficial or detrimental effects is currently unclear, not least because it is uncommon for these expressions to be assessed in the same participants.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation